Molybdenum Incorporation Induced Enhancement in the Mechanical Properties of Gallium Oxide Films. Issue 19 (19th July 2017) - Battu, Anil K.; Manandhar, Sandeep; Ramana, Chintalapalle V.
Abstract: An approach to design Ga2 O3 ‐based nanomaterials with tunable mechanical properties is presented. In the molybdenum (Mo) incorporated Ga2 O3 model system, where Mo content ( x ) is varied up to ≈11 at%, Mo‐incorporation induced effects are significant on the structural and mechanical properties. Single‐phase β‐Ga2 O3 formation occurs for lower Mo content (≤4 at%); however, higher Mo content induces the crystalline‐to‐amorphous structural transformation. Mechanical characterization reveals that the hardness of the Ga–Mo–O nanocrystalline films increases for Mo ≤ 10 at%, at which point hardness decreases due to Mo‐induced structural transformation. However, the elastic modulus of Ga–Mo–O decreases continuously with Mo incorporation. The Ga–Mo–O exhibits maximum H (≈36 GPa) for 10 at% Mo, where Mo‐incorporation induces enhancement in hardness as well as plasticity index parameter. Based on the results, a structure–composition–mechanical property correlation in Ga–Mo–O films is established. Abstract : An approach to design Ga2 O3 ‐based nanomaterials with tunable mechanical properties is reported. In the molybdenum (Mo) incorporated Ga2 O3 model system, where Mo content is varied up to ≈11 at%, Mo‐incorporation induced effects are significant on the structural and mechanical properties. Based on the results and analyses, a structure‐composition‐mechanical property correlation in Ga‐Mo‐O films is established.